Fixed Point Theorem on Weakly Compatible Mappings in Metric Space: Exploring weakly compatible mappings and their application in fixed point theorem (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The point of this paper is to introduce a common fixed point theorem in a metric space which sums up the aftereffect of P.C. Lohani and V.H. Badshah utilizing the more vulnerable conditions, for example, at times weakly compatible mappings and related sequence instead of compatibility and completeness of the metric space. Additionally, the state of continuity of any of the mappings is being dropped.